2010
DOI: 10.4111/kju.2010.51.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Fibroblast Growth Factor Receptor 3 in the Recurrence of Non-Muscle-Invasive Urothelial Carcinoma of the Bladder

Abstract: Purpose:The fibroblast growth factor receptor 3 (FGFR3) gene is known to be frequently mutated in noninvasive urothelial carcinomas of the bladder. In this study, we investigated the expression of FGFR3, Ki-67, and p53 in bladder cancers and the effects of expression on tumor recurrence. Materials and Methods: Fifty-five cases of primary bladder cancer were examined by immunohistochemistry. The relationship of these markers with various clinicopathological factors, including recurrence, was assessed. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
4
13
0
Order By: Relevance
“…Clinical studies are currently focusing on this HPV-positive subpopulation [37]. The FGFR3 amplification observed by the previous study in a mixed HPV-negative HNSCC cohort was not observed in the OSCC and OPSCC cohorts in this study [30]. An explanation could be that the FGFR3 gene is amplified in HNSCC tumors other than OSCC and OPSCC or gene amplification is not detected by our FISH analysis due to the arbitrarily selected ratio and cut-off values.…”
Section: Quantitative Reverse Transcription Polymerase Chainmentioning
confidence: 54%
See 1 more Smart Citation
“…Clinical studies are currently focusing on this HPV-positive subpopulation [37]. The FGFR3 amplification observed by the previous study in a mixed HPV-negative HNSCC cohort was not observed in the OSCC and OPSCC cohorts in this study [30]. An explanation could be that the FGFR3 gene is amplified in HNSCC tumors other than OSCC and OPSCC or gene amplification is not detected by our FISH analysis due to the arbitrarily selected ratio and cut-off values.…”
Section: Quantitative Reverse Transcription Polymerase Chainmentioning
confidence: 54%
“…This is in contrast to multiple myeloma and breast cancer, in which FGFR3 protein expression has been related to poor progression-free survival and overall survival [23,24]. For transitional cell carcinoma, the prognostic value for FGFR3 expression is still a subject of debate [18,19,[29][30][31][32][33][34].…”
Section: Quantitative Reverse Transcription Polymerase Chainmentioning
confidence: 99%
“…Six papers provided the relative risk (RR), and two articles provided OR values, which we used to estimate HR. Of the 31 studies, a significant association between high Ki-67 expression and poor RFS, PFS, OS and CSS was demonstrated in five [ 22 , 26 , 34 , 35 , 48 ], five [ 31 , 36 , 43 , 46 , 48 ], six [ 20 , 24 , 28 , 29 , 31 , 42 ] and seven studies [ 27 , 30 , 33 , 34 , 42 , 46 , 47 ], respectively. Of the literature, eleven, five, three and two studies linking Ki-67 expression with poor RFS [ 21 , 25 , 37 41 , 43 45 ], PFS[ 21 , 25 , 41 , 44 , 49 ], OS [ 23 , 32 , 41 ] and CSS [ 43 , 50 ], respectively, lacked statistical significance.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have investigated the use of FGFR3 expression as a predictor of prognosis in BC. While a number of authors were able to demonstrate a shorter RFS associated with FGFR3 expression ( 20 , 29 ), Gudjonsson et al ( 21 ) did not identify any difference in time to recurrence. In general, the role of molecular markers for predicting BC recurrence appears to be limited, as reviewed by van Rhijn ( 30 ).…”
Section: Discussionmentioning
confidence: 97%
“…The combination of WHO 2004 grading with FGFR3 mutation status facilitated improved risk stratification for patients exhibiting high-grade, non-muscle-invasive urothelial BC ( 5 ). However, studies of FGFR3 immunoreactivity and its clinical significance are uncommon ( 20 , 21 ). Immunohistochemical detection of the FGFR3 receptor may provide a simpler, cheaper and faster approach for histopathological practice, compared with the current method of determination of FGFR3 mutation status.…”
Section: Introductionmentioning
confidence: 99%